Development of E-LKPD Based on Problem Based Learning (PBL) Using Liveworksheet Website on Acid Base Material in High School - Putri, Salsabilla; Sitorus, Marham (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The problem of chemistry learning in high school during learning is that students find it difficult to understand the material and determine problem solving. Therefore, teaching materials are needed to overcome these problems. The purpose of this study is to produce E-LKPD based on Problem Based Learning using the Liveworksheet website on acid-base material in high school that is valid and practical for use by teachers in online learning activities. The type of research used is R&D (Research and Development) using the ADDIE model, namely (Analysis, Design, Development, Implementation, and Evaluation). The data analysis technique in this study uses qualitative descriptive and quantitative descriptive analysis techniques. This was obtained from the results of the analysis of the expert validation instrument material 78% and media 79% with a valid category, and the results of student responses obtained a practical percentage of 87%, while the results of the N-Gain trial were 72.29% with high criteria. Based on the results of the research and discussion, it can be concluded that the development of E-LKPD based on Problem Based Learning using the Liveworksheet website on acid-base material in high school is valid and very feasible to be used in learning activities.Keywords: Development, E-LKPD, PBL, Liveworksheet, Acid BaseDOI: 10.23960/jppk.v13i3.30472